Strengthening local institutions in the context of shifting policies - Eko Priyo Purnomo (School of Social and Int.Studies Univ.of Bradfo, 2014)
The research makes several recommendations. Firsty, the strengthening of local knowledge which is then adapted to new approachs within the local context> This would also require that Indonesian University scholars rethink how to study and develop konwedge based on Indonesian cntexts and culture. Scienteists should not be too ready to adopt "western" konwledge and eliminate their "own". Scondly, capacity building can be done at individual and communal levels and importantly applied using a bottom-up approach